2019
DOI: 10.1088/1755-1315/362/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Sediments in a Changing Environmental Conditions in Vistula Lagoon (Poland)

Abstract: The Vistula Lagoon has been evolving since its formation in the late Atlantic period. At the beginning, the changes were mainly driven by the stabilization of the Baltic Sea level, and the development of hydrographic network. Later on, anthropogenic activities have become an important factor. Hydrotechnical works conducted at the turn of the 20th century, aimed at regulating the outflow of the Vistula River waters, have significantly limited the riverine input into the lagoon. In the past, the Vistula Lagoon c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
4
0
2
Order By: Relevance
“…Это можно объяснить особенностями современной седиментации, для которой характерны активные процессы ресуспензии, являющиеся мощным механизмом самоочищения донных осадков [11]. При взмучивании сорбированные подвижные формы тяжелых металлов и иные поллютанты частично опять переходят из осадков в воду, частично с илистыми частицами выносятся в море [12,13].…”
Section: результаты исследования и их обсуждениеunclassified
“…Это можно объяснить особенностями современной седиментации, для которой характерны активные процессы ресуспензии, являющиеся мощным механизмом самоочищения донных осадков [11]. При взмучивании сорбированные подвижные формы тяжелых металлов и иные поллютанты частично опять переходят из осадков в воду, частично с илистыми частицами выносятся в море [12,13].…”
Section: результаты исследования и их обсуждениеunclassified
“…In (Chubarenko 1994), it is shown that resuspension can cover from 40 to 100% of the lagoon water area. The sedimentary material entering the lagoon is not fixed at the bottom immediately; it is repeatedly agitated with the resedimentation of bottom sediments and the partial removal of small fractions through the strait into the sea (Blazhchishin 1999;Szymczak 2019;Chechko 2017;Cieśliński 2013;Chechko V. 2008). In genetic terms, terrigenous sedimentary formations with a large range of dimensions -boulders, gravel, pebbles, mixed-grained sands, siltstones, and silt-pelitic silts are common on the bottom surface of the Vistula Lagoon (Chechko & Blazchishin 2002; Uścinowicz & Zachowicz 1966).…”
Section: Study Areamentioning
confidence: 99%
“…In the works devoted to studying the bottom sediments of the Vistula Lagoon, the primary attention was focused, as a rule, on their upper (0-10 cm) layer. The features of the spatial distribution of the main types of sediments on the bottom surface, their granulometric fractions, and the dynamics of the surface layer of bottom sediments were revealed (Szymczak 2019;Chechko 2017). However, the vertical structure of the sedimentary strata has been studied very poorly.…”
Section: Introductionmentioning
confidence: 99%
“…1-points for measuring the thickness of silt deposits using a geologist's drill; 2-sediment core sampling points; 3-Baltic strait; 4position of the Polish-Russian border In the works devoted to studying the bottom sediments of the Vistula Lagoon, the primary attention was focused, as a rule, on their upper (0-10 cm) layer. The features of the spatial distribution of the main types of sediments on the bottom surface, their granulometric fractions, and the dynamics of the surface layer of bottom sediments were revealed (Szymczak 2019;Chechko 2017). However, the vertical structure of the sedimentary strata has been studied very poorly.…”
Section: Introductionmentioning
confidence: 99%